2019
DOI: 10.1021/acs.jmedchem.9b00053
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Polypharmacological Melanocortin-3 and -4 Receptor Probes and Identification of a 100-Fold Selective nM MC3R Agonist versus a μM MC4R Partial Agonist

Abstract: The centrally expressed melanocortin-3 and melanocortin-4 receptors (MC3R, MC4R) are established targets to treat diseases of positive and negative energy homeostasis. We previously reported (J. Med. Chem. 60:4342 2017) mixture-based positional scanning approaches to identify dual MC3R agonist and MC4R antagonist tetrapeptides. Herein, 46 tetrapeptides were chosen for MC3R agonist screening selectivity profiles, synthesized, and pharmacologically characterized at the mouse melanocortin-1, −3, −4, and −5 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 85 publications
4
18
0
Order By: Relevance
“…An antagonist pA 2 value of 7.3 was observed for KNS2-22-4 at the mMC4R (Figure 3). In prior studies, this compound was observed to possess nanomolar agonist potency at the MC3R (30–40 nM), partial agonist stimulation of the MC4R, and sub-micromolar antagonist potency at the MC4R (pA 2 of 6.6–7) [40,41], similar to the results in the present study.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…An antagonist pA 2 value of 7.3 was observed for KNS2-22-4 at the mMC4R (Figure 3). In prior studies, this compound was observed to possess nanomolar agonist potency at the MC3R (30–40 nM), partial agonist stimulation of the MC4R, and sub-micromolar antagonist potency at the MC4R (pA 2 of 6.6–7) [40,41], similar to the results in the present study.…”
Section: Resultssupporting
confidence: 89%
“…The ( p Cl)DPhe-substituted KNS2-22-1 maintained similar potencies compared to KNS2-22-4 at the mMC1R and mMC5R, but was 9-fold less potent at the mMC3R (120 nM, Figure 2) and possessed an increased partial agonist response relative to NDP-MSH (70%, EC 50 = 280 nM) at the mMC4R (Figure 2) compared to KNS2-22-4 . The Ac-His-Arg-( p Cl)DPhe-Tic-NH 2 ( KNS2-22-1 ) tetrapeptide was previously reported to possess agonist pharmacology at the mMC3R (110 nM) and partial agonist activity at the mMC4R (EC 50 = 140 nM), similar to the values observed in the present study [41]. While similar potency relative to KNS2-22-4 was observed for the ( p F)DPhe-substituted KNS2-22-2 at the mMC1R, this substitution decreased potency at the mMC3R and mMC5R (30- and 14-fold as compared to KNS2-22-4 , respectively).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations